Nature and Memory in Tan Twan Engs Novels: An Ecocultural Perspective - Revathi a/p Gopal (Tanjung Malim, 2024)
Nature and Memory in Tan Twan Engs Novels: An Ecocultural Perspective by Revathi a/p Gopal